The Role of the Procurement Function in Realising Sustainable Development Goals: An Empirical Study of an Emerging Economy’s Oil & Gas Sector - Ekiugbo, Igho; Papanagnou, Christos (European Journal of Sustainable Development, 2017)
This research is motivated by the unsustainable nature of some oil and gas (O&G) firms’ activities, especially in developing countries and the dearth of research works about sustainable procurement (SP) within these countries. The O&G sector is characterized by complexity known to generate several negative impacts on humans and the environment. Our literature review reveals how SP practices can help improve the environmental, social and economic performance of practising firms, thereby leading to sustainable development of their immediate communities and the society in general. The aim of this research is to explore SP practices within the Nigerian O&G sector and to investigate how these practices can help firms achieve sustainable development goals. A questionnaire was used to collect primary data, which was analysed using exploratory factor analysis to ascertain the level of relationship between the research variables, consisting of environmental, social and economic aspects of sustainability. The research findings did not only indicate that some sustainable development goals (SDGs) can be achieved through the adoption of SP practices, but it also shows that the adoption of SP practices can help improve the performance of O&G companies. The result further indicates that government policies and regulations constitute a key driving force for firms to adopt sustainable practices. Keywords: Sustainable development, corporate sustainability, sustainable procurement, Oil & Gas, firm performance, Nigeria, developing countries.